Regulatory influence of α-Pinene on MATN3 expression in hepatocellular carcinoma: Extending to pan-cancer analysis - Binyu Zhao; Wenliang Qiu; Wenhui Xu; Lixin Wu; Jiayin Zhao; Haocheng Zhao; Fengxiang Wei; Bing Qiu (PLoS ONE, 2025)
In the search for novel therapeutic strategies against cancer, natural compounds such as α-Pinene, a bioactive monoterpene predominantly found in coniferous trees, have emerged as potential modulators of oncogenic processes. The primary objective of this study was to investigate whether α-Pinene can regulate the expression of MATN3 (Matrilin-3), a gene previously associated with poor prognosis in various cancers. Our central hypothesis is that α-Pinene exerts its anticancer effects, at least in part, by downregulating MATN3, thereby impacting oncogenic signaling. The rationale for selecting MATN3 as a target lies in its demonstrated overexpression in multiple cancer types and its established role as both a prognostic marker and a contributor to tumor progression. Extending our research through a comprehensive pan-cancer analysis, we confirmed the association between high MATN3 expression and poor prognosis across multiple cancer types. Further exploration revealed a strong correlation between MATN3 expression and immune infiltration, as well as significant associations with key immunomodulatory genes, suggesting an intricate role of MATN3 in the tumor immune environment. Enrichment analysis pointed to the involvement of MATN3 in the PI3K-AKT signaling pathway. Additionally, we identified connections between MATN3 and extracellular matrix (ECM)-related mechanisms.The downregulation of MATN3 by α-Pinene in HepG2 cells suggests a novel mechanism by which α-Pinene may exert anticancer effects, potentially through the disruption of key oncogenic and immune-related pathways. This study not only underscores the anticancer potential of α-Pinene but also establishes MATN3 as a critical target and biomarker across a spectrum of cancers. Our findings advocate for further clinical investigations into α-Pinene’s therapeutic potential, particularly focusing on its impact on MATN3 and related pathways in diverse cancer contexts.